2011 IEEE Symposium on Underwater Technology and Workshop on Scientific Use of Submarine Cables and Related Technologies 2011
DOI: 10.1109/ut.2011.5774096
|View full text |Cite
|
Sign up to set email alerts
|

Side-scan sonar image registration for AUV navigation

Abstract: peteR king/mUn mUn explorer AUV platform with the marine institute's holyrood marine base in the background.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 15 publications
0
22
0
1
Order By: Relevance
“…based on OpenCV. Features are typically matched using the strategy of nearest-neighbor distance ratio (NNDR), which was developed by Lowe [6] and the strategy of random sample consensus (RANSAC), which was developed by Fischler and Bolles [22]. Figure 7 shows two side-scan images at different scales obtained by side-scan sonar from the opposite direction, which are corrupted by noise.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…based on OpenCV. Features are typically matched using the strategy of nearest-neighbor distance ratio (NNDR), which was developed by Lowe [6] and the strategy of random sample consensus (RANSAC), which was developed by Fischler and Bolles [22]. Figure 7 shows two side-scan images at different scales obtained by side-scan sonar from the opposite direction, which are corrupted by noise.…”
Section: Resultsmentioning
confidence: 99%
“…Vanish used the scale-invariant feature transform (SIFT) algorithm with side-scan sonar image registration and found that it performed better than previous methods [6]. The SIFT algorithm, which was first developed by Lowe in [7], is perhaps the most important achievement in image matching.…”
Section: Introductionmentioning
confidence: 99%
“…Matching sonar images with high accuracy has been a unsolved problem for a long time [7] [1] [8]. This is due to specifics issues in sonar imaging, such as viewpoint dependence, non-uniform insonification, low signal-to-noise ratio, low resolution, and low feature repeatability [9].…”
Section: Related Workmentioning
confidence: 99%
“…This mechanism is very important for the detection and classification of bottom mines. Because of their very low target strengths, echoes from mines are very difficult to detect against a background of bottom reverberation; the shadowgraph can, however, indicate the presence of a mine even when its echo is hidden by the reverberation, see [9]- [10].…”
Section: Side Scan Sonar Operationmentioning
confidence: 99%